Aplikasi Kompos Daun Paitan (Tithonia diversifolia) Terfermentasi Ragi Tape Sebagai Pupuk Cair Terhadap Pertumbuhan dan Hasil Panen Bawang Dayak (Eleutherine Bulbosa) - Erliya Agus Trisna; Tatang Sopandi; Vivin Andriani (FMIPA : Universitas PGRI Adi Buana, 2022)
Soil fertility affects production which in turn uses dayak onion as a plant with low medicinal properties. Paitan leaf compost is known to be used as plant fertilizer that can improve soil fertility. This study aims to determine the effect of giving various concentrations of paitan leaf compost fermented by tape yeast on the growth and yield of dayak onions. The study was conducted experimentally using a completely randomized design (CRD) consisting of 6 treatments and 4 replications. The research was conducted in Grabagan Village, Tulangan District, Sidoarjo Regency. The treatments consisted of pearl chemical NPK fertilizer (16:16:16) as a positive control, without fertilization as a negative control, and 4 concentrations of paitan leaf compost, namely 10%, 20%, 30% and 40%. The results showed that fertilization had a significant effect (P<0.05) on leaf length, number of leaves, fresh weight and dry weight. The highest yield of fresh weight and dry weight of Dayak onions was obtained from paitan leaf compost fertilization with a concentration of 20%. Keywords: Dayak Onion (Eleutherine bulbosa), Paitan Leaf (Tithonia diversifolia), Tape Yeast, Paitan Leaf Compost Fertilizer